The antagonistic dynamic game based on repeating of the bimatrix game - Vakrinienė, S. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. П. Вакринене. Антагонистическая динамическая игра на основе повторения биматричной игры S. Vakrinienė. Antagonistinis dinaminis lošimas, kai kartojamas bimatricinis lošimas